“Percorso Giacomo”: An Italian Innovative Service of Perinatal Palliative Care - Locatelli, Chiara; Corvaglia, Luigi; Simonazzi, Giuliana; Bisulli, Maria; Paolini, Lucia; Faldella, Giacomo (Frontiers in Pediatrics, 2020)
The perspective proposed by this article will focus on perinatal palliative care as a strategy for improving the quality of life of neonates with life-limiting conditions when extending the patient’s life is no longer the goal of care. This manuscript reports the creation of an innovative program of perinatal palliative care called “Percorso Giacomo” (Giacomo’s Pathway) at Sant’Orsola Hospital in Bologna, Italy in 2013. Key features include interdisciplinary collaboration between professionals from obstetrics, neonatology and other specialties aiming to reach the most detailed fetal and neonatal diagnosis and prognosis; communication and engagement with the family to discuss goals of care and prepare a birthing plan that follows the family’s desires and expectations; and personalized care to achieve comfort for each newborn and support for families according to their social, cultural, and religious backgrounds.